Patterns of genomic variation in the poplar rust fungus Melampsora larici-populina identify pathogenesis-related factors - Persoons, Antoine; Morin, Emmanuelle; Delaruelle, Christine; Payen, Thibaut; Halkett, Fabien; Frey, Pascal; De Mita, Stéphane; Duplessis, Sébastien (Frontiers in Plant Science, 2014)
Melampsora larici-populina is a fungal pathogen responsible for foliar rust disease on poplar trees, which causes damage to forest plantations worldwide, particularly in Northern Europe. The reference genome of the isolate 98AG31 was previously sequenced using a whole genome shotgun strategy, revealing a large genome of 101 megabases containing 16,399 predicted genes, which included secreted protein genes representing poplar rust candidate effectors. In the present study, the genomes of 15 isolates collected over the past 20 years throughout the French territory, representing distinct virulence profiles, were characterized by massively parallel sequencing to assess genetic variation in the poplar rust fungus. Comparison to the reference genome revealed striking structural variations. Analysis of coverage and sequencing depth identified large missing regions between isolates related to the mating type loci. More than 611,824 single-nucleotide polymorphism (SNP) positions were uncovered overall, indicating a remarkable level of polymorphism. Based on the accumulation of non-synonymous substitutions in coding sequences and the relative frequencies of synonymous and non-synonymous polymorphisms (i.e. PN/PS), we identify candidate genes that may be involved in fungal pathogenesis. Correlation between non-synonymous SNPs in genes encoding secreted proteins and pathotypes of the studied isolates revealed candidate genes potentially related to virulences 1, 6 and 8 of the poplar rust fungus.